Use of Circle Game As A Strategy to Improve Students’ Vocabulary of Tenth Grade Of SMK Negeri 7 Bulukumba - Riswani, Riswani; Januarty, Restu; Muliati, Muliati (Lembaga Jurnal FKIP Universitas Bosowa, 2024)
The purpose of this study is to know how to improve students’ vocabulary on Circle Game at the tenth grade of SMK Negeri 7 Bulukumba. The researcher applied pre experimental in one class pre-test and post-test. In this research the population was the Tenth-grade students of SMKN 7 Bulukumba in 2023/2024 academic year. The researcher used total sampling technique. The total sample was 20 students from class X TKJ. In analyzing the numerical data, the writer used SPSS version 24.0. Based on the results of data analysis, the writer concluded that the use of Circle Game can increase students’ vocabulary knowledge, it’s proved by the mean score of the students’ in pretest and post-test. The result of the research shows that Circle Game significantly increased students’ vocabulary knowledge after did treatment where the results shown in the paired sample test are 0.001 is smaller than 0.05. The mean score improved from 49.75 in pre-test to 68.75 in post-test. It indicated that the one hypothesis (H1) was accepted and of course, the null hypothesis (H0) was rejected. It means that Circle Game can improve the students’ vocabulary knowledge in learning English at SMK Negeri 7 Bulukumba. Key Words: Circle Game, Strategy, Vocabulary